GE_GERICHTE C/27231/2008 vom 9. Juli 2009 - GE Cour de justice (2009)
REGISTRE DU COMMERCE ; ADRESSE; MODIFICATION(EN GÉNÉRAL) ; ORGANE(PERSONNE MORALE) ; DOMICILE EN SUISSE ; TYPE DE PROCÉDURE ; PROCÉDURE SOMMAIRE ; | CO.731.B. CO.718.4